2012
DOI: 10.1039/c2jm31174g
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of cells with silk surfaces

Abstract: Polymers are often employed in tissue engineering to replace damaged extracellular matrix (ECM). During the last few decades silk proteins have been extensively investigated concerning their use as biopolymers for the generation of biocompatible, artificial scaffolds. Including the low or absence of immune-response and lack of cell toxicity, silk proteins present interesting properties useful for tissue engineering and organ repair. Since cell-matrix interactions define the behaviour of cells and posterior gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 103 publications
1
75
0
Order By: Relevance
“…All rats of two experimental groups with spider silk-coated and uncoated miniaturized silicone implants, implanted into subcutaneous pockets (Figure 1 E), toxicity or immune reactions observed (unpublished data). Since it has been shown that eADF4(C16) can be processed into various morphologies such as fi lms, membranes and surface coatings, [ 12 ] here, medical grade silicone implants were coated with a micrometer thin eADF4(C16) layer (Figure 1 B). Further, the infl uence of the silk coating on biocompatibility of the implant and capsular fi brosis was investigated.…”
Section: Silk-coated Silicone Implants Are Well Tolerated In Spraquedmentioning
confidence: 99%
See 1 more Smart Citation
“…All rats of two experimental groups with spider silk-coated and uncoated miniaturized silicone implants, implanted into subcutaneous pockets (Figure 1 E), toxicity or immune reactions observed (unpublished data). Since it has been shown that eADF4(C16) can be processed into various morphologies such as fi lms, membranes and surface coatings, [ 12 ] here, medical grade silicone implants were coated with a micrometer thin eADF4(C16) layer (Figure 1 B). Further, the infl uence of the silk coating on biocompatibility of the implant and capsular fi brosis was investigated.…”
Section: Silk-coated Silicone Implants Are Well Tolerated In Spraquedmentioning
confidence: 99%
“…The genes of transforming growth factors β1, β2, and β3, responsible for triggering of cell proliferation, collagen www.afm-journal.de www.MaterialsViews.com wileyonlinelibrary.comsolution for 120 s and air drying for 120 s. This procedure induces β-sheet formation rendering the silk coating water insoluble. [10][11][12] All test items were subsequently rinsed with 0.9% w/v NaCl. Miniaturized implants for in vivo experiments were sealed in sterile containers together with 500 µL fresh 0.9% NaCl solution.…”
Section: Impact Of Spider Silk Coatings On Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…Unlike in nature, where spider silk proteins are typically processed into fibers, recombinant spider silk proteins can be processed into various other morphologies like particles, capsules, non-woven meshes or hydrogels. [1][2][3][4][5][6] It has previously been shown that the recombinant spider silk protein eADF4 can be processed into particles with controllable diameters by salting out. 1,2 Such silk particles consist of a solid core with high β-sheet content (around 60%) and a smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…The silk protein alone, while biocompatible, does not support neuronal adhesion due to the lack of specific protein sequences or epitopes recognized by cell membrane adhesive receptors. Moreover, at neutral pH silk fibroin has a net negative charge which affects the electrostatic interaction with the negatively charged cell membrane 21 . Therefore, silk scaffolds often require pre-coating to enhance adhesion of cells after seeding.…”
Section: Introductionmentioning
confidence: 99%